Thermodynamic patterns during in-situ heating of InAs nanowires encapsulated in Al2O3 shells. (22nd October 2021) - Yang, Hyun Ju; Choi, Suji; Kim, Jong Hoon; Kim, In; Ahn, Sang Jung; Lee, Ho Seong; Yi, Seong-Hoon; Kim, Young Heon
Abstract: Understanding the dynamic thermal behavior of nanomaterials based on their unique physical and chemical properties is critical for their applications. In this study, the thermal behavior of single-crystalline InAs nanowires in an amorphous Al2 O3 shell was investigated by conducting in situ heating experiments in a transmission electron microscope. Two different thermodynamic patterns were observed during the in situ heating experiments: (1) continuous vaporization and condensation simultaneously at temperatures lower than 838.15 K, and (2) pure evaporation at temperatures higher than 878.15 K. During the simultaneous condensation and vaporization in closer areas in a single InAs nanowire, the front edge of the vaporization was flat, while that of the condensation actively changed with time and temperature. Pure vaporization was conducted via layer-by-layer evaporation followed by three-dimensional vaporization at the final stage. The thermal behaviors of the InAs nanowires were demonstrated from a thermodynamic point of view.